The use of flax products processing in technology sponge cakes functional purpose - Dorohovich, Victoriya; Abramova, Asiat (My University, 2016)
The purpose of our work is to develop sponge cakes functionality. To achieve this task, we considered it appropriate to use in production technology sponge cakes processed flax (linseed meal), as flax is a natural source of ω-3 and ω-6 polyunsaturated fatty acids.
Keywords: функціональні продукти; the functional foods; бісквіти; sponge cakes; лляне борошно; flaxseed flour; кафедра готельно-ресторанної справи; кафедра технології хлібопекарських і кондитерських виробів